Isostatic compensation of Quaternary vertical crustal motions: coupling between uplift of Britain and subsidence beneath the North Sea. (22nd January 2016) - Westaway, Rob
ABSTRACT: New data from offshore and onshore regions confirm the view that the Quaternary uplift of Britain and subsidence beneath the North Sea are coupled, mediated by lower‐crustal flow induced by the lateral pressure gradient caused by climate‐driven surface processes. Most measured onshore uplift rates, in both upland and lowland localities, are only applicable since the Mid‐Pleistocene Revolution; beforehand, generally lower rates prevailed. Earlier (?Oligocene–Pliocene) phases of uplift and subsidence had typically even lower rates; furthermore, the western margin of the North Sea depocentre was ∼200 km farther from the modern coastline of north‐east England. In the earliest Cenozoic, complex isostatic adjustments occurred in response to the magmatism associated with the Iceland mantle plume; the contemporaneous land surface (relative to the present‐day rock column) in northern England was typically ∼1500 m OD. However, this activity died out during the Palaeogene; the main effect of these events on the modern isostatic configuration was via the emplacement of thick mafic underplating, which now constricts the mobile lower‐crustal layer, explaining the Late Cenozoic ultra‐stability of Ireland. The evidence enables interpretations of the present‐day topography of Britain as static, caused by the Iceland mantle plume, or actively developing in response to plate motions or plate boundary forces, to be excluded.